2020
DOI: 10.1002/ddr.21651
|View full text |Cite
|
Sign up to set email alerts
|

Effects of different doses of atorvastatin, rosuvastatin, and simvastatin on elderly patients with ST‐elevation acute myocardial infarction (AMI) after percutaneous coronary intervention (PCI)

Abstract: ObjectiveTo conduct a randomized double‐blind prospective study to investigate effect of different doses of atorvastatin, rosuvastatin, and simvastatin on elderly patients with ST‐elevation AMI after PCI.MethodsOne hundred and ninety‐two AMI patients over 60 years old who underwent PCI were randomly divided into six groups: the low atorvastatin group, high atorvastatin group; low rosuvastatin group; high rosuvastatin group; low simvastatin group; high simvastatin group. Demographic data and clinical informatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 15 publications
0
11
0
1
Order By: Relevance
“…Today, accelerated population aging has driven the constantly rising incidence of AMI and its increasing prevalence at younger ages; moreover, the disease progresses rapidly, which poses a serious impact on patients' physical and mental health and QOL and increases their economic burden [18]. Emergency PCI is the first choice to treat AMI, but due to the decline of patients' body function to varying degrees, it is prone to bring adverse effects on patients' mood and behavior, causing psychological problems such as preoperative anxiety and depression, thus affecting the efficacy of clinical treatment and nursing [19][20][21]. Routine nursing only focused on saving patients' lives, but ignored the changes of patients' emotional and psychological state, which affected patients' QOL [22,23].…”
Section: Discussionmentioning
confidence: 99%
“…Today, accelerated population aging has driven the constantly rising incidence of AMI and its increasing prevalence at younger ages; moreover, the disease progresses rapidly, which poses a serious impact on patients' physical and mental health and QOL and increases their economic burden [18]. Emergency PCI is the first choice to treat AMI, but due to the decline of patients' body function to varying degrees, it is prone to bring adverse effects on patients' mood and behavior, causing psychological problems such as preoperative anxiety and depression, thus affecting the efficacy of clinical treatment and nursing [19][20][21]. Routine nursing only focused on saving patients' lives, but ignored the changes of patients' emotional and psychological state, which affected patients' QOL [22,23].…”
Section: Discussionmentioning
confidence: 99%
“…However, two studies with relatively small sample sizes in Chinese showed that no significant differences of MACE and declined renal function between atorvastatin and other statins. 35 36 On the other hand, a large observational study in the USA found that 10 mg or 20 mg of atorvastatin use had lower cardiovascular (CV) event rates particularly in the first year of use than 20 mg or 40 mg of simvastatin 37 while another large observational study in the UK found that the risk of hepatotoxicity (small numbers of events observed) was increased in the first 6 months of atorvastatin compared with simvastatin treatment. 38 It might also be a reflection of the strong marketing activities that led to a better confidence in the brand among both doctors and patients, but we have no evidence to support this hypothesis and also it is beyond the scope of the current report.…”
Section: Discussionmentioning
confidence: 99%
“…We hypothesise that the good adherence to atorvastatin might be due to the better tolerability, and its efficacy and safety. However, two studies with relatively small sample sizes in Chinese showed that no significant differences of MACE and declined renal function between atorvastatin and other statins 35 36. On the other hand, a large observational study in the USA found that 10 mg or 20 mg of atorvastatin use had lower cardiovascular (CV) event rates particularly in the first year of use than 20 mg or 40 mg of simvastatin37 while another large observational study in the UK found that the risk of hepatotoxicity (small numbers of events observed) was increased in the first 6 months of atorvastatin compared with simvastatin treatment 38.…”
Section: Discussionmentioning
confidence: 99%
“…This may be because atorvastatin has a unique chemical structure, namely, aromatic groups, which form hydroxyl-activated metabolites that prolong the half-life of atorvastatin to improve vascular endothelial function, reduce cholesterol, and inhibit platelet aggregation, oxidation, and inflammation. They also increase other cardiovascular protective functions and regulate lipids, which can be further improved by enhanced-dose application [ 21 , 22 ]. For example, an enhanced atorvastatin dose reduces platelet aggregation and activation.…”
Section: Discussionmentioning
confidence: 99%